The Conservatories of Music facing the challenges arising from the pandemic - Rodríguez-Quiles, José A. (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The paper addresses the development of classes in Professional Music Teaching during the confinement caused by the pandemic. The difficulties that teachers had to face and the proposed solutions are also revealed. We are facing a qualitative research of a phenomenological nature in which nineteen teachers from Andalusia were interviewed. The results show the complexity of the virtualization of musical subjects. It is also evident that, despite the fact that the teaching staff is a firm supporter of face-to-face teaching, this historical fact could open the doors to new educational approaches not previously explored in the Conservatories.